Socialization Agents for Children - et al., Manjot Kaur Shah (International Journal of Advanced Science and Technology, 2019)
Children are important segment for marketers. Children these days are actively involved in the purchase process and are no more a passive users. Their voice is being recognized as a purchaser. They are both the purchaser of the products as well as the influencer. They have information about the market and various products in the market. There are many agents that contribute to the socialization process of the children. Both interpersonal and environmental agents play some role in the learning of the child. This paper attempts to analyze the various socialization agents for children. The study was conducted on 190 children in the age group of 6-12 years of age. The data was collected using structured questionnaire. The questionnaire was administered to the parents. The area of the study was Delhi.